New group key management framework for mobile ad hoc network based on identity authentication in elliptic curve field - DU Chun-lai; HU Ming-zeng; ZHANG Hong-li (Tongxin xuebao)
A new key management framework was proposed based on mutual identity authentication in elliptic curve field.Threshold scheme enhances system more stable.Mutual identity-based authentication guarantees node to communicate with the right one,by which the malicious nodes aiming to fake or send false information can be drawn away from MANET.